Hybrid Water Pump with River Flow and Solar Power for Farmer Groups in Plana Village-Banyumas Central Java - Jamrud Aminuddin; Rosi Widarawati; Petrus Hary Tjahja Soedibya; Maskhiyatus Shokib; Tika Ayunda Vita; Ulil Azmi; Dian Rizqi Saputra (Poltanesa, 2025)
Plana Village located in Somagede District, Banyumas Regency, Central Java Province is about 25 km Southeast of the Universitas Jenderal Soedirman Campus. In this village, a small business group is engaged in freshwater fish farming under the names TIRTA LESTARI and GAPOKTAN PLANA JAYA fish cultivator groups. Based on direct observations, the group uses the Serayu River as the primary water source for their fish ponds. The position of the fish pond is around 10 meters higher than the river flow so the water lifting process is carried out using a water pump. The only solution for providing water is to use a machine-powered water pump. The group complained about this solution because they had to pay operational costs for engine fuel. As a result, the group's profits are not optimized. Considering these conditions, a water pump technology transfer activity with a waterwheel as the driving force is planned to develop the results of research and service carried out in the Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Jenderal Soedirman.  The goal of the operations that have been conducted is to address partner concerns regarding the provision of water supplies. Activities aimed at becoming an economically productive partner will prioritize key issues, including the implementation of green energy technology, such as hybrid water pumps powered by solar energy and river flow. The next step involves providing training and counseling sessions for the TIRTA LESTARI agriculture group and the merged PLANA JAYA farming group.